Regulatory Evaluation Related to Managing The Spread of Covid-19 in Indonesia - Dwi Bagus Pambudi; Rela Pamungkas Sari; Risqi Dewi Aisyah (SOEPRA, 2021)
Abstract: Corona Disease 19 (COVID-19) virus infection originating from Wuhan in China over time has spread throughout the world including Indonesia. Various forms of regulations created in the form of legal instruments are one of the practical solutions that can solve this national problem. In line with the progress of these regulations with the Covid-19 case in Indonesia, it has not resulted in significant changes to reduce the number of cases of covid-19. The purpose of this article is to evaluate the regulations created in the response to the spread of Covid-19. The method used is a literature study using articles obtained from databases, implementation guidelines, the Republic of Indonesia Law, Minister of Health Regulations, Presidential Regulations and Government Regulations that fulfil the inclusion and exclusion criteria. The Government policies that are doubtful and even tend to be inconsistent is the one that causes ineffectiveness of these regulations in reducing the number of cases of the spread of Covid-19. Besides that, the lack of public understanding can lead to the various forms of violations in handling Covid-19 cases, because information knowledge plays an important role in influencing human behaviour.Keywords: Evaluation, Covid-19, handling, regulation Abstrak: Infeksi virus Corona Desease 19 (COVID-19) yang berasal dari kota Wuhan di China seiring berjalannya waktu menyebar ke seluruh dunia termasuk Indonesia. Berbagai bentuk regulasi diciptakan berupa instrumen hukum merupakan salah satu solusi praktis yang dapat menyelesaikan permasalahan nasional ini. Selaras dengan berjalannya regulasi tersebut dengan kasus Covid-19 di Indonesia tidak kunjung menimbulkan perubahan yang signifikan untuk menekan angka kasus penyebaran Covid-19. Tujuan dari artikel ini yaitu untuk mengevaluasi terkait regulasi yang diciptakan dalam penanggulangan penyebaran Covid-19. Metode yang digunakan yaitu studi literatur menggunakan artikel yang didapatkan dari data base, Pedoman Pelaksanaan, Undang-undang Republik Indonesia, Peraturan Menteri Kesehatan, Peraturan Presiden dan Peraturan Pemerintah yang memenuhi kriteria inklusi dan ekslusi. Kebijakan pemerintah yang meragukan bahkan cenderung tidak konsisten menjadi satu penyebab tidak efektifnya regulasi tersebut dalam menekan angka kasus penyebaran Covid-19 selain itu kurangnya pemahaman masyarakat dapat memicu berbagai bentuk pelanggaran dalam penanganan kasus Covid-19 karena pengetahuan akan informasi memegang peran penting dalam mempengaruhi perilaku manusia.Kata kunci : Evaluasi, Covid-19, Penanganan, Regulasi